Electrical Characterization of InN Nanowire/Si Heterojunctions. Issue 8 (18th March 2019) - Weiszer, Saskia; Jörg, Peter; Kolhep, Maximilian; Stutzmann, Martin
Abstract : This report deals with the electrical properties of a heterojunction between self‐assembled InN nanowires (NWs) grown by plasma‐assisted molecular beam epitaxy and Si (111) with different doping types and concentrations. Multiple NWs are contacted in a vertical sandwich structure and current–voltage (IU) measurements show a rectifying behavior which strongly depends on the doping level of the Si substrate. Comparable results are obtained for single NWs contacted with a conductive atomic force microscope tip. The transport processes can be described by thermionic emission theory of a Schottky diode. However, field emission and recombination can not be neglected, especially for high doping concentrations of the Si substrate. The temperature dependence of the barrier height and the ideality factor have been determined by measuring IU‐curves from 200 K up to 300 K. Furthermore, electrical changes based on aging and on different environmental conditions, like contact with water, are discussed. The underlying band diagram of the InN/Si heterojunction has been simulated with the software package Nextnano++ and is in agreement with the experimental data. The simulations consider both polarities of the InN NWs and both doping types of the Si substrates. Abstract : Current–voltage characteristics of InN nanowire/Si heterojunctions reveal a decreasing barrier height with increasing doping concentration of the Si substrate. A decreasing barrier height and ideality factor with aging is found, which might be caused by an increasing oxide shell. The environmental conditions have also an influence on the heterojunction usable for sensing applications. For p‐type Si, an increase of the barrier height with annealing is found, whereas the barrier decreases for n‐type Si.